INLAND WATER WAY TRANSPORTATION AS SAFETY AND ECONOMIC INTERVENTION PROJECT IN LAGOS - Irinyemi, Ademola (My University, 2024)
This study investigated the Lagos Inland Water Transportation from its perspectives as both safety and economic intervention project. The study objectives were availability, extent of use, safety and economic viability of this mode of transportation. The study made use of descriptive research design where both primary and secondary data were utilized. The researcher developed the study instruments to collect primary data from study respondents. Population for the study was 1400 respondents working in the inland water/maritime sub-sectors. Sample for the study was 140 respondents determined through the use of Yaro-Yemeni formular to reduce sampling error to the barest minimum. Statistical mean and standard deviation were used to answer the research questions. From the analysed data, it was revealed that there were unresolved issues about policy, investment, safety, economic viability among others. Based on these revelations, it was recommended that both Lagos State and the Federal governments should close ranks, work together to formulate and enforce quality policy, public/private investment synergy should be embraced, operators should take issues of safety more serious while being aware of need to make the sector viable and motivating, seeing its capital-intensive nature as both a challenge and an actuator